Fostering Intrinsic Motivation through Self Assessment; an Alternative in Improving Learning Quality - Muhimatul Ifadah; Siti Aimah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. The study aimed to stimulate students motivation through self assessment in improving learning quality. For this purpose, each student was given assessment sheet to make judgment about themselves for the whole semester. Alternative assessment is believed to have effective feedback for the students in the process of learning; its primary focus is on the ongoing development of the learners learning (Brown: 2004). The responses taken showed that the students in the early semester admitted that they have done the best, and gradually, they admitted that they need to improve their effort in the process of learning.In fact, personal motivation in the classroom setting is affected by various causes; one of others is triggered by the others judgment or can be by personal reflection. By filling personal judgment and reflection, the students are having chance to drawback their personal learning purposes.